Psychedelic Treatments for Psychiatric Disorders: A Systematic Review and Thematic Synthesis of Patient Experiences in Qualitative Studies - Breeksema, Joost J.; Niemeijer, Alistair R.; Krediet, Erwin; Vermetten, Eric; Schoevers, Robert A. (CNS drugs, 2020)
Introduction Interest in the use of psychedelic substances for the treatment of mental disorders is increasing. Processes that may affect therapeutic change are not yet fully understood. Qualitative research methods are increasingly used to examine patient accounts; however, currently, no systematic review exists that synthesizes these findings in relation to the use of psychedelics for the treatment of mental disorders. Objective To provide an overview of salient themes in patient experiences of psychedelic treatments for mental disorders, presenting both common and diverging elements in patients’ accounts, and elucidating how these affect the treatment process. Methods We systematically searched the PubMed, MEDLINE, PsycINFO, and Embase databases for English-language qualitative literature without time limitations. Inclusion criteria were qualitative research design; peer-reviewed studies; based on verbalized patient utterances; and a level of abstraction or analysis of the results. Thematic synthesis was used to analyze and synthesize results across studies. A critical appraisal of study quality and methodological rigor was conducted using the Critical Appraisal Skills Programme (CASP). Results Fifteen research articles, comprising 178 patient experiences, were included. Studies exhibited a broad heterogeneity in terms of substance, mental disorder, treatment context, and qualitative methodology. Substances included psilocybin, lysergic acid diethylamide (LSD), ibogaine, ayahuasca, ketamine and 3,4-methylenedioxymethamphetamine (MDMA). Disorders included anxiety, depression, eating disorders, post-traumatic stress disorder, and substance use disorders. While the included compounds were heterogeneous in pharmacology and treatment contexts, patients reported largely comparable experiences across disorders, which included phenomenological analogous effects, perspectives on the intervention, therapeutic processes and treatment outcomes. Comparable therapeutic processes included insights, altered self-perception, increased connectedness, transcendental experiences, and an expanded emotional spectrum, which patients reported contributed to clinically and personally relevant responses. Conclusions This review demonstrates how qualitative research of psychedelic treatments can contribute to distinguishing specific features of specific substances, and carry otherwise undiscovered implications for the treatment of specific psychiatric disorders.